A STUDY ON THE PROBLEMS OF WOMEN FISH VENDORS IN THOOTHUKUDI DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
Despite the enormous increase in the fisheries population there still exist poverty and financial instability in the life of fisherfolk in Tamil Nadu. They are at the lowest level of their profile in terms of their socio-economic conditions. Fisherfolk is almost neglected in the plan periods. Allotment to this vulnerable section is almost nil in the Government budgets. If this is being the case for the fishing community, the women from this smaller population escape the eyes of policymakers. Women play a key role in the development of the fisheries sector in addition to their role of sole household managers in most fisher families. Although the involvement of women is limited in capture fisheries, their supportive role in active fishing has increased manifold with the advent of mechanization and enhancement of multi-day fishing in marine fisheries. Women fish vendors are a small portion of this fisherfolk who believe in building up their status and giving education to their children by way of their hard work. Though these fish vendors work hard and are supported by the Government by way of financial inclusiveness there is no prosperity and development in the life of this section. The socio-economic and cultural backwardness of the fisherfolk should be analyzed from the point of view of their income and expenditure pattern The present study is an attempt to analyze the various issues related to women fish vendors in Thoothukudi District. A total of seventy-five fish vending women were selected for the study and the collected data were shown in percentage.